2016
DOI: 10.3748/wjg.v22.i30.6925
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor for ischemic-type biliary lesion after ABO-incompatible living donor liver transplantation

Abstract: High NK cell counts in a transplant recipient's blood are associated with ITBL after ABO-I ALDLT. Further research is needed to elucidate the molecular mechanism of NK cell involvement in the development of ITBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It may lead to intra- and extra-hepatic biliary stricture, bile duct injury and late graft loss, and is one of the reasons for retransplantation. [ 14 , 15 ] Several risk factors are discussed to be major parameters for the development of ITBL. Among them, prolonged ischemic times, reperfusion injury, disturbance in blood flow through the peribiliary vascular plexus, immunologically induced injury, cytotoxic injury, and ischemia reperfusion injury appear to have the most important influence.…”
Section: Discussionmentioning
confidence: 99%
“…It may lead to intra- and extra-hepatic biliary stricture, bile duct injury and late graft loss, and is one of the reasons for retransplantation. [ 14 , 15 ] Several risk factors are discussed to be major parameters for the development of ITBL. Among them, prolonged ischemic times, reperfusion injury, disturbance in blood flow through the peribiliary vascular plexus, immunologically induced injury, cytotoxic injury, and ischemia reperfusion injury appear to have the most important influence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a large number of NK cells in recipient peripheral blood was the only risk factor for the induction of ischemic biliary tract disease after ABO-incompatible adult living donor liver transplantation. This may be explained that recipient NK cells could recognize various NK cell ligands on the donor endothelial cells after flowing into the liver graft, and the ABO antigen was abundantly expressed on the endothelial cells of the transplant graft, thereby directly producing cytotoxicity and resulting in decreased graft survival ( 48 , 49 ). Besides, there is a clinical study suggesting that recipient-derived NK cells are reduced but retain the robust expression of NK cell receptors such as NKG2D in the early stage of pediatric liver transplantation, which may be closely related to the increase of acute graft rejection episode ( 50 ).…”
Section: Function Of Nk Cells In Hepatic I/rmentioning
confidence: 99%
“…ABOi deceased donor liver transplants are associated with a greater incidence of diffuse biliary strictures and in some series, inferior allograft survival, among adult recipients, but not young children . Several published series provide evidence of success among ABOi LDLT when there is modification of the preoperative and perioperative immunosuppression regimen with attention to isoagglutinin titers, but with an associated increased incidence of biliary complications . Furthermore, ABOi LDLT may not be ideal in certain clinical scenarios, particularly if the recipient has acute‐on‐chronic liver disease .…”
Section: Potential Indications For Lpementioning
confidence: 99%
“…(21)(22)(23) Several published series provide evidence of success among ABOi LDLT when there is modification of the preoperative and perioperative immunosuppression regimen with attention to isoagglutinin titers, but with an associated increased incidence of biliary complications. (21,(24)(25)(26) Furthermore, ABOi LDLT may not be ideal in certain clinical scenarios, particularly if the recipient has acute-on-chronic liver disease. (3) Except for young children, ABOi LDLT has not been performed in the United States, although 14 A2 donors have been used in non-A recipients (according to Organ Procurement and Transplantation Network/ UNOS data as of June 3, 2017).…”
Section: Abo Incompatibilitymentioning
confidence: 99%